Mobilising subterranean geopolitics: The spectre of spontaneous combustion and post mining imaginaries. Issue 130 (March 2022) - Hine, Amelia; Mayes, Robyn
Abstract: In the context of a groundswell of interest in developing innovative post-mining landscapes, this paper explores post-mining imaginaries through the example of a recently closed coal mine, Leigh Creek in South Australia. We explore how these imaginaries are put forward by the mine's local communities, multiple levels of government and the mining company itself. In this case, as occurs more broadly in coal mining, these imaginaries are co-constructed by the ever-present risk of underground spontaneous combustion—spon-com—as a result of mining practices. This article addresses the role of spon-com as not only a physical phenomenon of the underground, but as a socio-environmental mechanism wielding considerable political power in relation to post-mining possibilities. We contribute to the geopolitical discourse on the 'subterranean turn' by drawing on concepts of haunting-as-circumstance to explore the political agency of the underground to reach above and manipulate surface politics. We thereby complicate Maria de Lourdes Melo Zurita's identification of a pre-existing sub terra nullius that positions the subsurface as political nothingness awaiting human intervention. This is a crucial step forward in thinking through concepts informing understandings of surface–subsurface relations, including the introduction of spectral thinking within subterranean geopolitics. We thus advance scholarship on subterranean geographies by progressing concepts of inhuman agency grounded in a situated example of this agency in practice.